2017
DOI: 10.1002/hed.24732
|View full text |Cite
|
Sign up to set email alerts
|

Association between high expression of phosphorylated Akt and mammalian target of rapamycin and improved survival in salivary gland adenoid cystic carcinoma

Abstract: High level of Akt/mTOR activation in ACC is correlated with a significantly improved survival. P-mTOR and nuclear p-Akt are prognostic biomarkers of salivary gland ACC. © 2017 Wiley Periodicals, Inc. Head Neck 39: 1145-1154, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 53 publications
(60 reference statements)
1
7
1
Order By: Relevance
“…29 This study shows for the first time that high p-mTOR Ser2448 immuno-expression is significantly associated with recurrences and with lower DFS in patients with atypical meningiomas. Interestingly, differing from that reported in other neoplasias, [27][28][29] we did not observe any nuclear staining in the neoplastic cells of atypical meningiomas. Only one previous studies on p-mTOR Ser2448 immuno-expression in meningiomas clearly reported that subcellular localization of the protein could be nuclear and/or cytoplasmic.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…29 This study shows for the first time that high p-mTOR Ser2448 immuno-expression is significantly associated with recurrences and with lower DFS in patients with atypical meningiomas. Interestingly, differing from that reported in other neoplasias, [27][28][29] we did not observe any nuclear staining in the neoplastic cells of atypical meningiomas. Only one previous studies on p-mTOR Ser2448 immuno-expression in meningiomas clearly reported that subcellular localization of the protein could be nuclear and/or cytoplasmic.…”
Section: Discussioncontrasting
confidence: 99%
“…The prognostic role of p-mTOR Ser2448 immunoexpression has been analyzed in several neoplasias, and with contrasting results. Indeed, p-mTOR Ser2448 expression is a favorable prognostic factor in gastric cancer 27 or in salivary gland carcinoma, 28 while it is associated with bad prognosis in tongue squamous cell carcinoma. 29 This study shows for the first time that high p-mTOR Ser2448 immuno-expression is significantly associated with recurrences and with lower DFS in patients with atypical meningiomas.…”
Section: Discussionmentioning
confidence: 99%
“…Also, highly phosphorylated AKT levels in ACC tissue were associated with an increased risk for tumor relapse . In contrast, a recent publication showed that activation of AKT was also associated with better prognosis of salivary gland ACC patients . This discrepancy might arise because of distinct functions of the different AKT isoforms, suggesting the need for AKT isoform‐specific inhibitors in the treatment of salivary gland ACC patients .…”
Section: Discussionmentioning
confidence: 95%
“…Intriguingly, these studies revealed mutations in genes implicated in the PI3K‐AKT‐mTOR signaling cascade, suggesting a prominent role of this pathway in salivary gland tumorigenesis. Indeed, recurrent mutations resulting in activation of the PI3K‐AKT‐mTOR pathway were found in 30% of ACC, and activated (phosphorylated) AKT isoforms and downstream mTOR is enhanced in ACC as compared to healthy adjacent tissue .…”
Section: Introductionmentioning
confidence: 99%
“…NGF has been shown to play a role in tumour proliferation in OSCC and salivary adenoid cystic carcinoma (AdCC), which might be a reason for the cancer cells to migrate and invade the nerves. Ex vivo studies show that Akt is phosphorylated in AdCC suggesting that PI3K/Akt signalling pathway has an important role in salivary gland carcinogenesis . In this study, we aimed to investigate the role of NGF‐induced signalling pathway on PNI of oral and salivary gland tumours in vitro and to confirm the involvement of PI3K/Akt pathway in cellular scattering and migration via the use of MK2206 (Akt inhibitor).…”
Section: Introductionmentioning
confidence: 99%